Changes in physico-chemical properties, microstructure and intermolecular force of preserved egg yolk gels during pickling. (April 2019) - Yang, Yuan; Zhao, Yan; Xu, Mingsheng; Wu, Na; Yao, Yao; Du, Huaying; Liu, Haiyan; Tu, Yonggang
Abstract: Changes in physical and chemical properties, microstructure and intermolecular interactions of preserved egg yolk gels during pickling were determined to clarify the formation mechanism of alkali-induced egg yolk gels. The pH, hardness, springiness, and cohesiveness of exterior egg yolks (hardened portion) increased firstly and then decreased, but moisture content decreased. The pH and viscosity of interior egg yolks (viscous portion) increased gradually, moisture content and oil exudation increased firstly and then decreased. Oil exudation of exterior egg yolks has similar trend with interior egg yolks. T21 and T22 of interior egg yolks obtained from LF-NMR spin-spin relaxation times decreased firstly and then increased. While T21 and T22 of exterior egg yolks showed an opposite trend and then increased at late state of pickling. Scanning electron microscopy (SEM) and Transmission electron microscopy (TEM) observed that interior egg yolk particles were ruptured and aggregated again, and exterior egg yolks gradually formed a dense and fiber gel network structure. Electrophoresis results showed that there was different degree degradation from interior to exterior egg yolks. Secondary structure contents contained numerous β-structure, regardless any portions of preserved egg yolks. However, exterior egg yolks had no thermal transformation, while interior egg yolks had significant thermal transformation, revealing the residual enthalpy decreased. The results suggested that the three-dimensional structure of exterior egg yolk gels was maintained by ionic bonds (71%), hydrophobic interaction (10%) and disulfide bond (10%), whereas the mainly intermolecular forces of interior egg yolk are ionic bond (80%) and the hydrogen bond (12%). Graphical abstract: Highlights: Interior egg yolks gradually form ordered yolk aggregations and granules. Exterior egg yolks gradually form compact gel network structure. Multiple interactions between protein molecules and interactions between proteins and lipids.